1989
DOI: 10.1159/000234735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Systemic and Orally Administered Iota-Carrageenan on Ovalbumin-Specific Antibody Response in the Rat

Abstract: Iota-carrageenans are high molecular weight polygalactans commonly used in the food industry. Their immunomodulating effects were examined on the reaginic and IgG ovalbumin-specific responses after systemic or oral administration to Brown Norway rats. Intraperitoneal injection of ovalbumin with either iota-carrageenan or alum induced both a reaginic and IgG response. Reaginic antibodies were detected in the primary response with alum, but only in the secondary response with iota-carrageenan. Oral tolerance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Carrageenan is used as a component to induce non-specific inflammation, possibly through activation of innate immune responses. It modulates acquired immunity, adjuvant and suppressive effects (Coste et al, 1989;Macino and Morelli, 1983;Bash and Vago, 1980;Nicklin and Miller, 1984;Cochran and Baxter, 1984;Vijayakumar et al, 1990). In our results, we observed that CAR stimulated-macrophages displayed a remarkable increase (142-75%) of nitric oxide production as compared to nonstimulated cells and a significant increase of about 50-33% as compared to the macrophages collected from mice stimulated with LPS.…”
Section: Discussionsupporting
confidence: 57%
“…Carrageenan is used as a component to induce non-specific inflammation, possibly through activation of innate immune responses. It modulates acquired immunity, adjuvant and suppressive effects (Coste et al, 1989;Macino and Morelli, 1983;Bash and Vago, 1980;Nicklin and Miller, 1984;Cochran and Baxter, 1984;Vijayakumar et al, 1990). In our results, we observed that CAR stimulated-macrophages displayed a remarkable increase (142-75%) of nitric oxide production as compared to nonstimulated cells and a significant increase of about 50-33% as compared to the macrophages collected from mice stimulated with LPS.…”
Section: Discussionsupporting
confidence: 57%
“…Carrageenan is widely used by the food industry due to its gelling and stabilizing properties, and it has been extensively used as a reagent to induce non‐specific inflammation, possibly through activation of innate immune responses. Carrageenan has also been ascribed the property of modulating acquired immunity, and both adjuvant and suppressive effects have been reported [2–7]. Such inconsistent outcomes may be due to differences in the route of administration, dosage and heterogeneity of carrageenan preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports describe the modulation of acquired immunity by carrageenan, where both adjuvant and suppressive effects are observed. Adjuvant effects are usually obtained by systemic administration of carrageenan, resulting in augmentation of antibody responses [2, 3]. On the contrary, several studies demonstrate that both systemic and oral administration of carrageenans suppress antibody production and mitogen‐induced T cell proliferation [4–7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported similarly diminished lymphocyte responsiveness in presence of carrageenan, without a visible modification, or a toxic effect on intraepithelial lymphocytes or lymph node T cells (3,7,13). To explain low lymphocyte responsiveness, several authors implicated a role for macrophages (8,14).…”
Section: Discussionmentioning
confidence: 68%
“…Although large amounts of oral carrageenan induce colitis (5,6), small quantities do not appear to be toxic for the gut mucosa (3). Studies in rats have demonstrated an adjuvant effect similar to alum when carrageenan was given with ovalbumin by systemic route, but abrogation of the PCA response when given orally (7). Diminished cellular immune response mediated by carrageenan has also been demonstrated in other models.…”
mentioning
confidence: 96%